Restoration of Gnetum edule (Willd.) Blume: A threatened medicinal plant of wet tropical biome in India - Sharma, Bhagwati Prashad; Barman, Hiranmoy; Das, Kadambini; Sampatrao, Tambe Satish; Kumar, Arvind; Kumar, Sanjeet (Indian Forester, 2025)
No Abstract.